Gross Morphological and Morphometrical Studies on the First and Second Coccygeal Vertebrae of Blue Bull (Boselaphus tragocamelus) - Sathapathy, S.; Dhote, B. S.; Mahanta, D.; Tamilselvan, S.; M. Mrigesh; Joshi, S. K. (International Journal of Livestock Research, 2019)
The present study was carried out on the first and second coccygeal vertebrae of six specimens of adult Blue bull (Boselaphus tragocamelus). They presented complete arches and spinous processes. The transverse processes were found to be plate like that were directed downward, backward extending beyond the level of the posterior articular surface of the body. There were two intervertebral foramina in the cranial aspect of Cy1 in Blue bull. The left one was smaller having 0.05±0.001 cm and 0.008±0.001 cm diameter, whereas the right one was larger having 0.11±0.002 cm and 0.15±0.001 cm diameter. The ventral spine was bifid forming sulcus vasculosus for the passage of the middle coccygeal artery.